Enhancing Vibration Reduction on Lightweight Lower Control Arm. (23rd October 2020) - Messana, Alessandro; Ferraris, Alessandro; Airale, Andrea G.; Fasana, Alessandro; Carello, Massimiliana
Abstract : This paper describes the design procedure to enhance the damping properties of a multimaterial lightweight suspension arm for a C-segment vehicle. An innovative viscoelastic material has been used to join carbon fiber with steel that has a function of passive constrained layer damper and adhesive simultaneously. Therefore, the hybrid technology applied has been focused on reducing the LCA mass, diminishing the steel thickness, and adding a CFRP tailored cover without compromising the global mechanical performance. Particular attention has been paid to the investigation of the dynamic response in terms of vibration reduction, especially in the range of structure-borne frequencies of 0–600 Hz. Two different viscoelastic materials have been evaluated in such a way to compare their stiffness, damping, and dynamic properties. The experimental test results have been virtually correlated with a commercial FEM code to create the respective material card and predict the real behavior of the LCAs (original and hybrid). The experimental modal analysis has been performed and compared on both the arms highlighting a very good correlation between virtual and experimental results. In particular, the hybrid LCA allows an interesting improvement of damping ratio, about 3, 5 times higher for each eigenmode than in the original solution.